2016
DOI: 10.1007/s12665-015-4901-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wetting rate and simulated rain duration on soil crust formation of red loam

Abstract: The characteristics of crusts are closely related to soil erosion in red loam under a rainfall condition. To better manage crust-prone soils and to accurately predict hydrological processes, it is necessary to understand the mechanism of crust formation. Wetting rate is an important factor influencing soil aggregate stability and crust formation. In this study, we considered two factors, wetting rate (slow 2 mm h -1 , fast 50 mm h -1 ) and rainfall quantity (intensity of 60 mm h -1 with every 5 min as a treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In contrast to the results of soil loss, the amount of runoff water in this study was not affected by the presence of surface mulching. The direct impact of the rainfall did not decrease the infiltration rate of the surface layer in BA and CA plots, which might occur by the formation of crust or clogging (Han et al, ). This result is clearly different from the results in other studies that showed surface mulching decreased runoff coefficient compared with that in the control plots without mulch (Gholami et al, ; Keesstra et al, ; Prosdocimi et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the results of soil loss, the amount of runoff water in this study was not affected by the presence of surface mulching. The direct impact of the rainfall did not decrease the infiltration rate of the surface layer in BA and CA plots, which might occur by the formation of crust or clogging (Han et al, ). This result is clearly different from the results in other studies that showed surface mulching decreased runoff coefficient compared with that in the control plots without mulch (Gholami et al, ; Keesstra et al, ; Prosdocimi et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Eldridge believed that this process requires one year in situations of suitable rainfall [29], while Bresson believed that a physical crust is likely to form after one or two rainfall and drying events [22]. In Han's study, the crusts formed rapidly under laboratory conditions (within one hour) [44]. Regardless, these researchers all agree that a physical crust can dramatically decrease the infiltration rate.…”
Section: Role and Function Of Physical Crusts In The Infiltration Ratmentioning
confidence: 96%
“…First, to better study the temporal evolution of infiltration on recent landslides, it is necessary to understand the formation mechanism and duration of physical crusts. Previous studies have assumed that raindrop impacts are the main driver of physical crust formation [44,45] and that the rainfall intensity influences the physical crust thickness. Simulated rainfall experiments have shown that the crust thickness slowly increases with increasing rainfall intensity [45,46].…”
Section: Role and Function Of Physical Crusts In The Infiltration Ratmentioning
confidence: 99%
“…For this study, crust strength was measured with two instruments, commonly used to describe soil resistance to erosion: a fall cone penetrometer for both fields-as experimental crusts, and a torvane for only the field crusts. Fall cone penetrometer measurements have been used by several studies [68][69][70][71][72]. The major advantage of using a fall cone penetrometer was the small scale of the measurement, both in surface and in depth.…”
Section: Crust Strength Measurementsmentioning
confidence: 99%